PRODUCTION OF CHEMICALS WITH GENETICALLY MODIFIED ESCHERICHIA COLI STRAINS FROM RENEWABLE RESOURCES - FAZAKAS, Andrea; CSATÓ-KOVÁCS, Erika; BODOR, Zsolt; LÁNYI, Szabolcs; ÁBRAHÁM, Beáta (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The main aim of this study was to create mutant strains with lambda Red recombination system from an Escherichia coli strain which was isolated from animal faeces. E. coli Ter8/1 strain was genetically modified using lambda Red recombination system and two mutant strains were obtained, TerP01, in which the gene of pyruvate formate lyase was inactivated, and TerPL02, in which the genes of pyruvate formate lyase and lactate dehydrogenase were inactivated. The analysis of product formation in dual-phase fermentation and in minimal salts medium with three carbon sources was performed. The first mutant, TerP01, produced a large amount of lactic acid with small amount of byproduct formation. In the case of the second mutant, TerPL02, lactic acid production has been finished and succinic acid production increased significantly.